2012
DOI: 10.1016/j.jbiomech.2012.07.024
|View full text |Cite
|
Sign up to set email alerts
|

European Society of Biomechanics S.M. Perren Award 2012: The external mechanical environment can override the influence of local substrate in determining stem cell fate

Abstract: The aim of this study was to explore how cell-matrix interactions and extrinsic mechanical signals interact to determine stem cell fate in response to transforming growth factor-β3 (TGF-β3). Bone marrow derived mesenchymal stem cells (MSCs) were seeded in agarose and fibrin hydrogels and subjected to dynamic compression in the presence of different concentrations of TGF-β3. Markers of chondrogenic, myogenic and endochondral differentiation were assessed. MSCs embedded within agarose hydrogels adopted a spheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 57 publications
3
40
0
Order By: Relevance
“…The subcutaneous environment differs in a number of notable ways to the orthotopic environment. Mechanical cues, absent in the subcutaneous environment, such as hydrostatic pressure [59][60] and dynamic compression [61][62] have been shown to play a role in regulating the endochondral phenotype of MSCs as well as matrix production [63].…”
Section: Discussionmentioning
confidence: 99%
“…The subcutaneous environment differs in a number of notable ways to the orthotopic environment. Mechanical cues, absent in the subcutaneous environment, such as hydrostatic pressure [59][60] and dynamic compression [61][62] have been shown to play a role in regulating the endochondral phenotype of MSCs as well as matrix production [63].…”
Section: Discussionmentioning
confidence: 99%
“…2), may explain the large accumulation in sGAG during culture in chondrogenic conditions. Unlike alginate, fibrin permits cell mediated integrin binding [33] and a more spread MSC morphology [34], which in turn may support robust osteogenic [35] and/or endochondral differentiation. This may explain why in contrast to alginate and chitosan constructs, which calcified preferentially around their periphery upon culture in hypertrophic conditions, fibrin constructs facilitated a homogenous deposition of calcium in vitro while accumulating the highest levels of calcium when normalized by % wet weight.…”
Section: Micro-computed Tomographymentioning
confidence: 99%
“…Thorpe et al [16] isolated bovine chondrocytes ( 6×10 6 ), which were seeded into rhCII gels (rhCII-cell) and subsequently injected subcutaneously into the back of nude mice. The results demonstrated that extra cellular matrix stained heavily with toluidine blue and had strongly positive collagen type II immunohistochemical staining.…”
Section: Collagenmentioning
confidence: 99%
“…In repairing cartilage defects, there appears an evidence that fibrin is not as useful as other well developed hydrogels, [16] because bone marrow mesenchymal stem cells (BMSCs) and adipose derived stem cells (ADSCs) showed a diminished chondrogenic potential when encapsulated in fibrin. [16,33,34] Therefore, we need further functionalize this versatile injectable hydrogel system to optimize for cartilage repair therapies.…”
Section: Fibrinmentioning
confidence: 99%
See 1 more Smart Citation